Video Search and Mining - Schonfeld, Dan; Shan, Caifeng; Tao, Dacheng; Wang, Liang (Studies in Computational Intelligence, 2010)
This book provides an overview of emerging new approaches to video search and mining based on promising methods being developed in the computer vision and image analysis community. Video search and mining is a rapidly evolving discipline whose aim is to capture interesting patterns in video data. It has become one of the core areas in the data mining research community. In comparison to other types of data mining (e.g. text), video mining is still in its infancy.The objective of this book is to present the latest advances in video search and mining covering both theoretical approaches and practical applications. The book provides researchers and practitioners a comprehensive understanding of the start-of-the-art in video search and mining techniques and a resource for potential applications and successful practice. This book can also serve as an important reference tool and handbook for researchers and practitioners in video search and mining.